2021
DOI: 10.1007/s00405-021-07098-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal COVID-19 and neonatal hearing loss: a multicentric survey

Abstract: Purpose Gestational SARS-Cov-2 infection can impact maternal and neonatal health. The virus has also been reported of causing sensorineural hearing loss. The objective of this study was to determine the possible effect of maternal SARS-COV-2 infection on neonatal hearing as identified during universal hearing screening. Methods Retrospective cohort study in two tertiary referral centers including all neonates born from November 2020 through April 1st, 2021 and undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
(46 reference statements)
3
17
1
Order By: Relevance
“… The absence of HL in the study does not rule out the possibility that SARS-CoV-2 infection causes congenital HL. Uncertain Poor Mostafa et al [27] 2021 Egypt Retrospective study November 2020 to April 1st, 2021 34 NA TEOAE, ABR Although 29 cases failed the initial hearing screening, only 1 case (2.9 %) failed when retested. It seems no increased risk of HL in newborns.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… The absence of HL in the study does not rule out the possibility that SARS-CoV-2 infection causes congenital HL. Uncertain Poor Mostafa et al [27] 2021 Egypt Retrospective study November 2020 to April 1st, 2021 34 NA TEOAE, ABR Although 29 cases failed the initial hearing screening, only 1 case (2.9 %) failed when retested. It seems no increased risk of HL in newborns.…”
Section: Resultsmentioning
confidence: 99%
“…In the second place, 2 related papers were published from Italy [22] , [29] . Besides, there is 1 paper each from the United States and Egypt [25] , [27] . The distribution of countries where the study was conducted is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations